2020
DOI: 10.2166/bgs.2020.914
|View full text |Cite
|
Sign up to set email alerts
|

Water quality performance of a permeable pavement and stormwater harvesting treatment train stormwater control measure

Abstract: Stormwater runoff from urban development causes undesired impacts to surface waters, including discharge of pollutants, erosion, and loss of habitat. A treatment train consisting of permeable interlocking concrete pavement and underground stormwater harvesting was monitored to quantify water quality improvements. The permeable pavement provided primary treatment and the cistern contributed to final polishing of total suspended solids (TSS) and turbidity concentrations (>96%) and loads (99.5% for TSS). B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…Valinski and Chandler [18] showed that permeable pavement with asphalt mixture and Portland concrete as a surface presented filtering rates greater than native soils. It has been shown that permeable interlocking concrete pavement can reduce stormwater runoff [10,19,20] and can filter and decrease pollutants concentrations [15,[17][18][19][20][21][22][23][24][25][26]. Even the possibility of using a permeable pavement system to treat greywater for irrigation and toilet flushing has been studied [27]; it was found that permeable pavements can work as a treatment and storage unit in greywater reuse schemes, but they are inefficient in reducing total aerobic and total coliform bacteria.…”
Section: Reservoir Coursementioning
confidence: 99%
“…Valinski and Chandler [18] showed that permeable pavement with asphalt mixture and Portland concrete as a surface presented filtering rates greater than native soils. It has been shown that permeable interlocking concrete pavement can reduce stormwater runoff [10,19,20] and can filter and decrease pollutants concentrations [15,[17][18][19][20][21][22][23][24][25][26]. Even the possibility of using a permeable pavement system to treat greywater for irrigation and toilet flushing has been studied [27]; it was found that permeable pavements can work as a treatment and storage unit in greywater reuse schemes, but they are inefficient in reducing total aerobic and total coliform bacteria.…”
Section: Reservoir Coursementioning
confidence: 99%
“…Conventionally, percolation is assumed to recharge groundwater and contribute to baseflow through subsurface hidden paths [60]. Yet, lateral seepage from the bioretention is not negligible, and it can be comparable to ET amount [64] or even a much more dominant term than both ET and vertical percolation [65]. The fate of the lateral seepage has not been extensively studied yet, which could end up being intercepted by downstream rooting systems and eventually released into the air by ET again, instead of reaching the channels as baseflow.…”
Section: Baseflow Regulationmentioning
confidence: 99%
“…Among them, mass-balance tracking is most often adopted due to its simplicity and cost-effectiveness. Mass balance can be tracked indirectly by interpreting the variations in moisture content or ponding water such as in permeable pavement [85], green roof [90], and bioretention cases [65] or, more often, directly monitored by the weight change via a lysimeter. These methods generally focus on a small piece of GI and by various degrees block moisture, momentum, and energy exchanges between the monitored piece and the unmonitored environment.…”
Section: Measurement Of Evapotranspiration From Green Infrastructurementioning
confidence: 99%
“…It will also cause a lack of investment in the maintenance of roads -pit and landing. An assessment of the impact factors and environmental effects on asphalt and concrete pavements was presented by Winston et al (2020) [8]. Two specific case studies were analysed here, each with alternatives available for pavement construction, the traditional flexible pavement designed according to national standards versus the modern steel-fibres (SFR-RCC)-Compressed concrete paving.…”
Section: Introductionmentioning
confidence: 99%
“…These alternatives were analysed using the GABI Programme to assess their environmental aspects related to the concept of sustainability as well as the effects of environmental factors on both models. Following a detailed discussion of the main findings obtained in these studies, conclusions and recommendations were formulated for an adequate selection of building alternatives [8]. In the present paper, the main issue discussed is the floods and rainfall effects on roads, and a redesign of road geometry is performed using accurate engineering formulas and design conditions.…”
Section: Introductionmentioning
confidence: 99%